Sang cipta rasa agung mosque: analysis of culture spiritual values as religious citizens - Apriyanda Kusuma Wijaya; Bambang Yuniarto; Ratna Puspitasari; Wulan Andini; Yayuk Hidayah (Universitas Tanjungpura, 2023)
This study aims to determine the spiritual values of culture that are reflected in the Great Mosque of Sang Cipta Rasa Cirebon, the method used is ethnography with a qualitative approach, while the data collection techniques used are interviews, observation and documentation. Place of research at the Great Mosque of Sang Cipta Rasa Cirebon. The informants in this study were the takmir of the mosque who was one of the elders of the mosque to obtain information about cultural history and various religious activities at the mosque, then several mosque congregations to obtain data on religious values, and guides senior tour at the Cirebon Kasepuhan Palace to strengthen data and information related to the history, culture and religious values depicted from the mosque. Data analysis techniques use data reduction, data presentation, and data verification. The Sang Cipta Rasa Great Mosque is one of the special mosques for the people of Cirebon, from a spiritual aspect of culture this mosque is a place of worship for congregational prayers, during Friday prayers there is Adzan Pitue, as a religious tourist spot for the history of the development of Islam in Cirebon, this mosque is also is the result of the acculturation of Javanese and Sundanese culture. The cultural nuance is increasingly attached because the location of this mosque is in front of the Cirebon Kasepuhan Palace. The Great Mosque of Sang Cipta Rasa is a manifestation of religion and culture in Cirebon